Rheology, dispersion, and cure kinetics of epoxy filled with amine‐ and non‐functionalized reduced graphene oxide for composite manufacturing. Issue 8 (15th September 2021) - Ackermann, Annika C.; Carosella, Stefan; Rettenmayr, Markus; Fox, Bronwyn L.; Middendorf, Peter
Abstract: This study evaluates the effect of plasma surface functionalization of reduced graphene oxide particles on the processing characteristics and homogeneity of dispersion of a bisphenol A‐(epichlorhydrin) epoxy matrix and amine‐based hardener with varying weight fractions from 0.00 to 1.50 wt%. It was observed that amine‐functionalized reduced graphene oxide leads to a more drastic viscosity increase of up to 18‐fold of the uncured suspensions and that its presence influences the conversion rates of the curing reaction. Optical microscopy of thin sections and transmission electron microscopy analysis showed that a more homogeneous dispersion of the particles could be achieved especially at higher weight fractions by using an appropriate surface functionalization. This knowledge can be used to define suitable processing conditions for epoxies with amine‐based hardeners depending on the loading and functionalization of graphene‐related particles. Abstract :